2023
DOI: 10.1177/15533506231165830
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Microwave Scissors-Based Off-Clamp Laparoscopic Partial Nephrectomy in a Porcine Model

Abstract: Objectives To assess the feasibility of off-clamp laparoscopic partial nephrectomy using microwave scissors. Methods We performed transperitoneal laparoscopic partial nephrectomy, without hilar clamping or renorrhaphy, using only microwave scissors for renal resection in a porcine model. For each kidney, 2 types of procedures were performed: a middle pole resection excising an area of 2-cm diameter and approximately 1-cm depth and a lower pole resection at the level of the lower polar line. The renal calyces e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although the usefulness of off-clamp MSPN was demonstrated, its procedural success might be attributed to the open-surgery modality because the MWS was omnidirectionally manipulated, facilitating tissue coagulation and bleeding control in a short time. To inspect the impact of degrees of freedom on MWS manipulation in the minimally invasive surgery modality, we conducted a preliminary experiment in five kidneys from three pigs ( 21 ) following the present study. It demonstrated that off-clamp sutureless laparoscopic partial nephrectomy (LPN) using MWS is feasible for both middle and lower pole resections, mimicking various tumor locations in clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the usefulness of off-clamp MSPN was demonstrated, its procedural success might be attributed to the open-surgery modality because the MWS was omnidirectionally manipulated, facilitating tissue coagulation and bleeding control in a short time. To inspect the impact of degrees of freedom on MWS manipulation in the minimally invasive surgery modality, we conducted a preliminary experiment in five kidneys from three pigs ( 21 ) following the present study. It demonstrated that off-clamp sutureless laparoscopic partial nephrectomy (LPN) using MWS is feasible for both middle and lower pole resections, mimicking various tumor locations in clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Even though hilar clamping was not performed, the off-clamp sutureless LPN using MWS ( 21 ) recorded shorter PT and lesser BL compared to porcine on-clamp LPNs ( 37 , 38 ), in which renal bleeding was controlled with renal suturing ( 37 , 38 ), renal suturing with hemostatic agents ( 38 ), or electrocautery with hemostatic agents ( 37 ), respectively. In addition, its BL ( 21 ) was lesser than that of off-clamp open PN using ultrasonic ( 39 ) or radiofrequency ablation devices ( 39 ), in similar porcine renal resections reported previously. To our knowledge, the cost of MWS is lower than that of other devices usually employed for dissection in conventional LPN, such as bipolar radiofrequency or ultrasonic devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation